2015
DOI: 10.1111/apt.13445
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: predicting and optimising response to anti‐TNF therapy in Crohn's disease – algorithm for practical management

Abstract: Nonresponse or loss of response to anti-TNF occurs commonly in Crohn's disease. Clinical algorithms utilising therapeutic drug monitoring may establish the mechanisms for treatment failure and help guide the subsequent therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
221
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(229 citation statements)
references
References 140 publications
(214 reference statements)
3
221
1
4
Order By: Relevance
“…Considerable strides have been made towards understanding how best to utilize and monitor these agents, yet up to 30% of patients will fail to initially respond, and among those who do respond, nearly half will lose response over time ( 1 ). Furthermore, the use of these agents is not without risk, and treatment may be limited by adverse events (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable strides have been made towards understanding how best to utilize and monitor these agents, yet up to 30% of patients will fail to initially respond, and among those who do respond, nearly half will lose response over time ( 1 ). Furthermore, the use of these agents is not without risk, and treatment may be limited by adverse events (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Immunogenicity failure, pharmacodynamic failure and pharmacokinetic failure must be distinguished [53,54]. Immunogenicity failure is characterized by lack of improvement of symptoms in the setting of decreased drug levels and formation of anti-drug antibodies (ADA).…”
Section: What To Do In Case Of Anti-tnf Failure?mentioning
confidence: 99%
“…In pharmacodynamic failure drug levels are normal and ADA are absent. In pharmacokinetic failure drug levels are decreased and ADA are absent [53]. A special situation of pharmacokinetic failure is the setting of acute severe UC.…”
Section: What To Do In Case Of Anti-tnf Failure?mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we have to mention a recent systematic review by Ding et al who found that smoking status has been associated with primary nonresponse and secondary loss of response to anti-TNF therapy, although the examined studies did not include just operated patients with absent disease, but those with ongoing active illness, in whom the natural history of CD had been already influenced by environmental and other factors such as smoking. 5 In conclusion, the above data suggest that, although smoking cessation remains of paramount importance in preventing CD recurrence, anti-TNF drugs may effectively counteract the effect of cigarette smoking on postoperative disease relapse, and its major detrimental effect on CD natural history should be re-evaluated by considering that the majority of available data up to date are based on studies carried out with drugs (i.e. thiopurines and mesalazine) that have been shown to be poorly effective in modifying the natural history of CD.…”
mentioning
confidence: 99%